2016
DOI: 10.1002/pat.3805
|View full text |Cite
|
Sign up to set email alerts
|

Influence of modified mesoporous silica SBA‐15 on the flammability of intumescent high‐density polyethylene

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 52 publications
2
11
0
Order By: Relevance
“…Phosphorus-containing FR materials which are integrated into polymer matrix without covalent bonds, tends to decompose beyond 250°C due to less stable bonds of PÀ OÀ C than CÀ C bond hence accelerates the degradation of polymer matrix. [31][32][33] Same phenomenon was observed in our experiments. Both T 5 wt % and T max wt % values had decreased while the amount of flame retardant material doped MPSs had increased.…”
Section: Thermal Stabilitysupporting
confidence: 89%
“…Phosphorus-containing FR materials which are integrated into polymer matrix without covalent bonds, tends to decompose beyond 250°C due to less stable bonds of PÀ OÀ C than CÀ C bond hence accelerates the degradation of polymer matrix. [31][32][33] Same phenomenon was observed in our experiments. Both T 5 wt % and T max wt % values had decreased while the amount of flame retardant material doped MPSs had increased.…”
Section: Thermal Stabilitysupporting
confidence: 89%
“…One of the most important ways to improve the flame retardancy of polyolefins is to use an intumescent flame retardant (IFR), which is generally composed of ammonium polyphosphate (APP) and pentaerythritol (PER) . 2,3 During combustion, the APP/PER generates a protective char layer on the surface, thereby inhibiting the transfer of mass, flammable gases, and heat to prevent the underlying matrix from further burning 4,5 . However, the intumescent formulation alone cannot provide the desired flame‐retardant properties for commercial use.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon‐containing materials have been also used widely as eco‐friendly flame‐retardants with no phosphorus 44–51 . It has been reported that the presence of silicon element in a flame‐retardant material has improved the thermal stability of the char layer formed during combustion 44,48,50,52 .…”
Section: Introductionmentioning
confidence: 99%
“…Mesoporous silica materials, such as MCM‐41 and SBA‐15, are largely studied because of facile synthesis, ease of successive functionalization, highly ordered nanostructure, large surface area, and uniform and tailorable pore size 53,54 . Mesoporous silica‐based materials have attracted the attention of many researchers in the field of flame retardancy in recent years 44,45,51,55,56 . High surface area, uniform and large pore size, special open‐pore structure, and the presence of SiOH active sites make mesoporous silica more conducive to toxic smoke suppression and molecular capture.…”
Section: Introductionmentioning
confidence: 99%